Water Quality for Florists—Why is it so Important - Gast, Karen L. B. (My University, 2000)
This publication describes water quality and how florists use water to be succesful.
MF2436_2000_03
Keywords: MF2436; Environment and Natural Resources; Lawn and Garden; MF